Ddidactic strategies to promote the development of speaking skills in seventh-grade students at escuela de educación básica Matilde Hidalgo De Prócel, cantón La Libertad, province of Santa Elena, school year 2021-2022 - Yumbo Grefa, Nélida Adelaida (2021)
English is the world’s main language, which has allowed people to communicate in an effective way throughout all countries in the world. However, Teaching English adds value to the educational system worldwide. That is why, educators must design didactic strategies to teach English, as for example Tongue twisters, that are traditional tools. In this sense, the objective is to propose didactic strategies to develop oral communication skills for English language through tongue twisters on 7th-grade students of the Matilde Hidalgo de Prócel school. The methodology applied was based on quantitative research with a non-experimental design. The research question is How do didactic strategies influence to improve speaking skills? To collect information a survey was structured with questions intended for students. In which, many answered that teachers use dialogues to improve speech, attendance was limited by an hour of English class per week, etc. For this reason, the propose was to create a didactic guide using Tongue twisters as a technique to improve pronunciation and speaking skills.